A shear wall element for nonlinear seismic analysis of super-tall buildings using OpenSees - Lu, Xinzheng; Xie, Linlin; Guan, Hong; Huang, Yuli; Lu, Xiao (Finite elements in analysis and design, 2015)
Numerical simulation has increasingly become an effective method and powerful tool for performance-based earthquake engineering research. Amongst the existing research efforts, most numerical analyses were conducted using general-purpose commercial software, which to some extent limits in-depth investigations on specific topics with complicated nature. In consequence, this work develops a new shear wall element model and associated material constitutive models based on the open source finite element (FE) code OpenSees, in order to perform nonlinear seismic analyses of high-rise RC frame-core tube structures. A series of shear walls, a 141.8-m frame-core tube building and a super-tall building (the Shanghai Tower, with a height of 632m) are simulated. The rationality and reliability of the proposed element model and analysis method are validated through comparison with the available experimental data as well as the analytical results of a well validated commercial FE code. The research outcome will assist in providing a useful reference and an effective tool for further numerical analysis of the seismic behavior of tall and super-tall buildings. •A new shear wall element model is proposed and implemented in OpenSees.•Shear wall element model is validated using published experimental data.•A modeling strategy is developed for simulating super-tall buildings using OpenSees.•Simulation of tall buildings is validated using well accepted commercial FE code.•A 42-story RC building model is accessible online to allow the work to be reproduced.